Hedonism Lifestyle on The Behavior of Visiting Tourism Objects During The Covid-19 Pandemic - Yenita Yenita; Fransisca Iriani Roesmala Dewi; Mario Devotyasto (Graduate Program of Universitas Tarumanagara, 2023)
The influence of a hedonistic lifestyle on the behavior of those visiting tourist attractions during the pandemic turned out to have quite an impact on the level of individual hedonism in several age groups. A hedonistic lifestyle comes from negative emotions that arise from within each individual who has a desire to buy the product or service he likes. Of course, the changes in the impact that occurred in the COVID-19 pandemic have limited the number of visits and reduced costs, causing the behavior of tourists visiting tourist attractions during the COVID-10 pandemic to be very high. This study is qualitative research by conducting interviews with tourists who visit tourist attractions during the pandemic. This study involved six participants who were willing to be interviewed. The data analysis technique uses an interactive model of qualitative data analysis from Miles and Huberman, namely data reduction, data presentation, and conclusion drawing or verification, which are interactively interconnected during and after data collection. This study aims to explore the factors that encourage the emergence of a hedonistic lifestyle in consumer behavior when visiting tourist attractions. One of the factors is the individual's desire to be satisfied in a culinary destination by buying the product or service he likes. Based on the results of the study, the main factor that supports a hedonistic lifestyle is a high enough income so that a person can buy whatever they want without thinking too much. Most of the participants expressed no remorse or coercion in fulfilling these wishes. It's all based on the high needs of life and self-satisfaction.